Global commodity governance : state responses to sustainable forest and fisheries certification - Gale, Fred; Haward, Marcus (International political economy series, 2011)
"The Forest and the Marine Stewardship Councils constitute new global governance institutions using voluntary certification and labelling as market incentives to encourage sustainable management. Utilizing a comparative political economic framework, the authors analyze shifting British, Canadian and Australian responses to the stewardship councils"